Integrating Islamic Education Values into School Curricula to Foster Students’ Digital Ethics: Implications for Educational Management - Ridlo, Muhammad ‘Ainur; Abdullah (Journal of Educational Management Research, 2026)
The rapid development of digital technology presents new ethical challenges in education, such as social media misuse and low digital moral awareness. This study aims to examine how Islamic Education (PAI) values can be integrated into school curricula to foster students’ digital ethics, while considering educational management dimensions. A qualitative descriptive approach was employed, utilizing in-depth interviews, participatory observation, and document analysis involving teachers, students, and school leaders. The findings reveal three main patterns: internalization of spiritual values through digital literacy, cross-subject collaboration in applying Islamic values, and habituation of digital ethics within the school culture. Integrating PAI values enhances students’ moral awareness and digital responsibility. The study’s contribution lies in proposing a value-based curriculum model that aligns spiritual education with digital competence. Practically, schools are encouraged to strengthen teacher training and implement curriculum policies that promote ethically responsible digital literacy.